(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Drug addiction is one of the most significant issues in our country. Millions of people suffer from drug addiction and abuse due to various factors, such as peer pressure, the influence of acquaintances, the influence of family members, or the result of curiosity. Drug addiction leads to biological, psychological, health, and social issues due to drug abuse. The researchers focused on the area of Payatas. This study aimed to identify factors affecting the increase in drug abuse in Payatas. The researchers used the descriptive method and the random sampling technique. The researchers surveyed the barangay staff, normal residents, police authorities, and people who recovered from drug addiction. Most respondents were 18-21, male, single, and degree holders. Most respondents agreed that drug affects a person’s social ability because it affects relationships, the workplace, social media, the environment, and neighbourhoods. The respondents approved the recommendations the researchers proposed.